Self Reported Musculoskeletal Pain Among Dentists (2011)
Background: Musculoskeletal complaint is an important health issue among dentists. Given the significance of this topic, we considered it necessary to investigate the prevalence and impact of musculoskeletal disease among Nigerian dentists Aim/Objectives: To assess the work- related complaints among dentists with the specific objective of finding out the prevalence of neck and back pain among dentists Materials and Methods: A structured questionnaire was sent to tivo hundred and fifty practising dentists in 3states capitals which were randomly selected from South - Western Nigeria. Participants were drawn from general hospitals, private clinics and teaching hospitals. Participants included general practitioners, specialists in restorative dentistry, oral and maxillofacial surgery, child oral health (pediatric and orthodontists), period ontology and oral pathology. Results: The response to participate in the study was 66.7% out of which 60% correctly filled questionnaire was analyzed. The mean age of participants was 32.8 ± 6.8years (SD) with a male to female ratio of 1.4:1. Prevalence of back pain was 89.6% while that of neck pain was 81.3%. Back pain was found to be higher in females (91.7%) compared to males (88.1%) while neck pain was higher in males (82.1%) compared with to females (80.0%). Back and neck pain were highest in those who worked 8-12 hours per day. Back pain was highest(94A%) in those who had practiced for 6-10 years while those who had practiced for more than 20 years reported *the highest percentage of neck pain. Respondents in restorative dentistry all had back pain at one time or the other over a period of twelve months, while neck pain was highest among respondents in child oral health(91.7%) . 43% of respondents perform their procedures standing, while 38% use the sitting position and 19% alternate between standing and sitting position. Other work related complaints reported by the dentists include headache, shoulder pain, pain around the wrists and paresthesia of the fingers of the dominant hand More respondents missed work due to back pain irrespective of the gender. 17 respondents sought medical help due to neck pain out of which 8(47.1%)) received only analgesics while among those who sought medical attention due to back pain, 7(63.7%) received analgesics only. Conclusions: Occupational related health problems among Nigerian dentists were common. There is a substantial need and demand for further training in occupational health and safety among dentists.